Knowledge and Awareness Regarding Flipped Classroom among Undergraduate Dental Students in Khammam - Himaja, Dr. Ch.; Pratap, Dr. K. V. N. R.; Padma, Dr. T. Madhavi; Kumar, Dr. V. Srujan; Singh, Dr. Surbhit (International Journal Of Drug Research And Dental Science, 2025)
The flipped classroom is an innovative teaching model that shifts direct instruction outside the classroom through videos or readings, allowing in-class time for active learning and collaboration. This approach promotes student engagement, deeper understanding, and self-paced learning. Research indicates that the flipped model can improve academic performance and critical thinking skills, though challenges such as technology access and adaptation remain. Overall, the flipped classroom enhances modern education by fostering interactive and student-centered learning. Aim: The aim of the study is to evaluate the knowledge and awareness about flipped classroom among undergraduate dental students in khammam. Objectives Promote Active Learning: Shift from passive lectures to interactive, discussion-based, and hands-on activities. Enhance Student Engagement: Increase participation and motivation through collaborative and problem-solving tasks. Improve Knowledge Retention: Allow students to review materials at their own pace, reinforcing understanding. Develop Critical Thinking Skills: Encourage deeper analysis, questioning, and application of concepts. Method A cross-sectional survey was conducted among 240 dental students, comprising 132 male (55%) and 108 female(48%), including 15 first-year BDS students,30 second-year BDS students, 27 third-year BDS students, 64 final year BDS students and 104 interns. The survey included 13 questions exploring Knowledge and awareness on flipped classrooms among dental students. Responses were analysed based on gender and year of study using chi-square test, P-value to identify statistical significant differences.